2007
DOI: 10.1097/olq.0b013e318074e565
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Bacterial Vaginosis in the United States, 2001–2004; Associations With Symptoms, Sexual Behaviors, and Reproductive Health

Abstract: Objectives: Bacterial vaginosis (BV), a disturbance of vaginal microflora, is a common cause of vaginal symptoms and is associated with an increased risk of acquisition of sexually transmitted infections,HIV, and with adverse pregnancy outcomes. We determined prevalence and associations with BV among a representative sample of women of reproductive age in the United States.Study Design: Women aged 14 -49 years participating in the National Health and Nutrition Examination Survey 2001-2004 were asked to submit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
408
7
10

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 584 publications
(441 citation statements)
references
References 27 publications
16
408
7
10
Order By: Relevance
“…Figure 4 shows the clue cells. This is comparable to the study of Koumans et al [9] who had also found a 29.2%…”
Section: Methods Of Collectionsupporting
confidence: 91%
“…Figure 4 shows the clue cells. This is comparable to the study of Koumans et al [9] who had also found a 29.2%…”
Section: Methods Of Collectionsupporting
confidence: 91%
“…En el mundo, el África Subsahariana registra las prevalencias más altas de VB, sobre todo en las zonas afectadas por el virus de la inmunodeficiencia humana (VIH). En Norteamérica, una de cada tres mujeres tienen VB (1) . En Latinoamérica, Chile reporta hasta un 32% (2) en tanto que en adolescentes del Brasil se reportan prevalencias de más de 30%, ya sea con pruebas de pH y KOH, o con puntaje de Nugent (3) .…”
Section: Introductionunclassified
“…19,20,24 Büyük örneklemli bir çalışmada, lezbiyenlerde BV (%45,2) prevalansı heteroseksüel gruba (%28,8) göre daha yüksek bulunmuştur. 25 Kadın cinsel partner ve BV arasındaki ilişkiyi inceleyen sistematik çalışma ve meta-analiz sonuçları, kadın seks partnerine sahip olan kadınlarda BV gelişme riskinin iki kat fazla olduğunu göstermektedir. 13 Vajinal sıvı değişimi ya da kadın partnerler arasındaki diğer paylaşılan davranışlar BV oluşumuna katkı da bulunabilmektedir.…”
Section: Sağlik Ri̇skleri̇unclassified